2018
DOI: 10.1111/lcrp.12125
|View full text |Cite
|
Sign up to set email alerts
|

The psychological impact of solitary: A longitudinal comparison of general population and long‐term administratively segregated male inmates

Abstract: Purpose. This study expands upon existing research on the psychological impact of administrative segregation on inmates by addressing several methodological limitations in this body of literature.Methods. Using a pre-post design, this study compared male general population (GP) inmates in the United States to those with up to 4 years in segregated placement across scores on the MCMI-III.Results. While segregated inmates reported higher levels of distress (particularly on measures of anxiety, depressed mood, po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 42 publications
1
29
1
Order By: Relevance
“…This, along with controlled studies (17,23,52,57,58), indicates that inmates with a known mental illness are not driving the entirety of the association between SC and psychological distress. Lastly, some studies observed that whereas general population inmates improved over time on measures of psychiatric symptoms, SC inmates remained stable (52,56). If most inmates are indeed improving with time (54), stability in SC could be viewed as its own negative outcome.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…This, along with controlled studies (17,23,52,57,58), indicates that inmates with a known mental illness are not driving the entirety of the association between SC and psychological distress. Lastly, some studies observed that whereas general population inmates improved over time on measures of psychiatric symptoms, SC inmates remained stable (52,56). If most inmates are indeed improving with time (54), stability in SC could be viewed as its own negative outcome.…”
Section: Discussionmentioning
confidence: 88%
“…Symptoms were either evaluated as part of correctional clinical evaluations (51), by trained graduate students (33,54) or selfreported by inmates (52,55). The database was characterised by FIGURE 1 | Flowchart of the search strategy to identify the 13 studies included in systematic review and 7 studies in meta-analysis.…”
Section: Psychological Symptomsmentioning
confidence: 99%
“…The results of the O’Keefe et al (2013) and Zinger et al (2001) studies failed to show evidence of increased psychological distress and mental health symptomatology in AS inmates compared with general population inmates, whereas results from the Chadick et al (2018) study offered no support for the assertion that placement in AS inevitably leads to psychological deterioration in those who receive such treatment. These findings are inconsistent with the founding tenets of SHU syndrome and the notion that long-term confinement in restrictive housing aggravates mental health symptomatology (Blanchette, 2001; Brodsky & Scogin, 1988; Haney, 2003; Jackson, 2001).…”
Section: Literature Reviewmentioning
confidence: 84%
“…In what is probably the most recently published study on restrictive housing and psychological deterioration, Chadick, Batastini, Levulis, and Morgan (2018) examined a sample of 48 adult male offenders remanded to the custody of the Kansas Department of Corrections (KDOC). The 24 inmates sampled from restrictive housing, where they had been living for past 1 to 4 years, were matched on age, ethnicity, primary psychiatric diagnosis, and most severe crime with 24 general population inmates.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation